Exchange-rates - real and monetary factors - Purvis, Dd (Economic & Social Studies, 1982)
Precis: In this paper we explore several alternative models of the exchange rate which highlight the role played by real and monetary factors in exchange rate determination, and the short-and long-run effects of exchange rate changes on real output. In the first model, attention is focused on the role of purchasing power parity (PPP) with flexible prices and a variable real exchange rate. The second model introduces sticky prices and replaces PPP with interest rate parity as the key short-run link to the international economy. The third model introduces a multi-sector production structure and explores the implications of Marshallian dynamics whereby capital stocks adjust only slowly. Finally, some conclusions about the role of stabilisation policy are offered.
Keywords: Economics; Sociology